The Interactional Styles Used by Male and Female Chairpersons in Petra Christian University Student Executive Board Meetings - Anila Cinantya; Herwindy Maria Tedjaatmadja (Kata Kita: Journal of Language, Literature, and Teaching, 2014)
This study examines the interactional styles related to the role of chairperson used by two female and two male chairpersons in the SEB-PCU meetings. There are three main theories used: interactional styles, gender, and chairpersons and their roles in a meeting. The method used is qualitative approach focusing on the process and the data. The findings reveal that both feminine and masculine interactional styles were used by the chairpersons. The masculine interactional styles were employed to play the roles of chairpersons. The use of interactional styles between female and male chairpersons differs in its ratio although the same linguistic clue was used for the same device. Here, conciliatory feature was not produced by the male chairpersons whereas referentially oriented feature was produced frequently by chairpersons. Overall, it proves that females use more feminine interactional styles while males use more masculine interactional styles. Thus, gender and power play an important role in meeting.